Case Report: Late paradoxical intrapulmonary shunt after endoscopic lung volume reduction with endobronchial valves for severe emphysema - Dzuko Kamga, Jacques; Gut Gobert, Christophe; Egenod, Thomas; Guibert, Nicolas; Le Roux, Pierre-Yves (Frontiers in Medicine, 2025)
Endoscopic endobronchial valve lung volume reduction in the management of severe emphysema reduces volume inflation in the most severely affected areas, with the hope of clinical improvement. We report the case of a patient who presented with late progressive respiratory deterioration following endoscopic endobronchial valve lung volume reduction. Ventilation/perfusion (V/Q)-SPECT/CT showed unexpectedly high perfusion in the atelectasis of the treated lobes, reflecting a paradoxical intrapulmonary shunt. This paradoxical complication of endobronchial valve treatment for severe emphysema is rare and highlights the potential usefulness of performing V/Q-SPECT/CT imaging in patients presenting with respiratory deterioration following endoscopic lung volume reduction.